Readings in British monetary economics - Johnson, Harry G. (Oxford : Clarendon Press, 1972)
The book contains the works of scholars on the Money study group of Radcliffe conference. It examines the subjects of money and economic activity, the demand and supply of money, financial intermediaries, debt management and monetary policy.
Includes index
usc 28/06/2017
Loans
Keywords: Monetary policy; Great Britain